Developing high quality end-of-life care in nursing homes: an action research study - Hockley, Jo M. (The University of Edinburgh, 2006)
This thesis provides an account of an action research study undertaken to develop staff knowledge concerning high quality end-of-life care for older people resident in nursing homes. Two independent nursing homes (NH1, NH2a & NH2b) volunteered to take part. In each nursing home, an exploratory phase was undertaken using focus groups, interviews, participant observation, and documentary analysis. This exploratory work confirmed specific contextual and clinical issues related to end-of-life care and highlighted that dying was peripheral to the nursing home culture where the emphasis was on functional rehabilitation. In each home, an initiative, inductively derived from discussion with staff and based on the exploratory phase, was devised and implemented. In the first nursing home, the initiative entailed development of'collaborative learning groups' (CLGs) which took place following the death of a resident; in the second home, the adaptation and introduction of an 'integrated care pathway (ICP) for the last days of life' to be used prior to the death of a resident, provided a system around which high quality end-of-life care could be promoted. Both actions were evaluated. These initiatives enabled a greater openness towards death and dying in both nursing homes.

A model for developing practice is presented combining these two inductively derived initiatives that acknowledge the importance of both the lifeworld of staff in their care of dying residents and their families and the nursing home system. This model, and the process of undertaking the action research, is discussed in relation to Habermas's Theory of Communicative Action - a substantive theory of 'system' and 'lifeworld'. Implementing the ICP as an integral part of a system for end-of-life care within the rehabilitative culture of nursing homes, and facilitating learning through a CLG after a resident dies, both (and importantly, together) encourage the development of staff knowledge and their support of each other in their care of dying residents. Previous research studies in this area of care have, in the main, only described the quality of endof-life care in nursing homes; a few studies have tried to influence such care through education and clinical involvement. This study makes a contribution to knowledge on the basis of it being an action research study in two nursing homes focused on the process of trying to change a functionally orientated rehabilitative culture to one that is more open to staff needs in the delivery of high quality end-of-life care. Findings of the study are discussed in relation to wider political and development issues; namely, the responsibility that nursing homes now have in the end-of-life care of older people; the importance of greater openness by management of nursing homes in their recognition of death and dying as an integral part of the culture and their subsequent support of staff; the unique role that nurses in nursing homes have to promote quality end-of-life care; and the need for targeted practice development initiatives within nursing homes to encourage better knowledge of symptom control and end-of-life issues that are specific to the care of older people dying in nursing homes.